2017
DOI: 10.1038/nature24023
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA repair pathway choice in S and G2 phases by the NHEJ inhibitor CYREN

Abstract: Classical non-homologous end joining 1 (cNHEJ) and homologous recombination 2 (HR) compete for the repair of double stranded breaks of DNA during the cell cycle. HR is inhibited in G1 phase of the cell cycle, but both pathways are active in S and G2 phases. Why cNHEJ does not always outcompete HR in S and G2 phases has been unclear. Here we show that CYREN is a cell cycle specific inhibitor of cNHEJ. CYREN suppression allows cNHEJ at telomeres and intrachromosomal breaks during S and G2 phases, while cells lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
195
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 40 publications
(40 reference statements)
3
195
0
Order By: Relevance
“…Genetic studies in mice complement these biochemical findings as it was found that an XLF DNA-PKcs double knockout is synthetically lethal (19). Interestingly, a Ku70 knockout rescues this synthetic lethality (105).…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 59%
See 1 more Smart Citation
“…Genetic studies in mice complement these biochemical findings as it was found that an XLF DNA-PKcs double knockout is synthetically lethal (19). Interestingly, a Ku70 knockout rescues this synthetic lethality (105).…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 59%
“…1). A small protein called CYREN [cell cycle regulator of NHEJ (69 aa); also called MRI-2, a sub-peptide of C7orf49 (157 aa)] has been proposed to affect Ku DNA binding (not specified how) and thus favor the HR pathway choice in S/G2 (19), though the data on CYREN effects on Ku binding are conflicting (20). Signaling factors appear to be important in controlling resection, as there is evidence that the DNA damage response protein p53-binding protein 1 (53BP1) is antagonistic to end resection, acting through a number of effector proteins (21,22).…”
Section: Overview Of Nhej In Humans and Its Relationship With Other Pmentioning
confidence: 99%
“…Ku-APLF interaction was shown to facilitate recruitment of the APLF-partner XRCC4 at damaged sites 9 and was proposed to stabilize the assembly of NHEJ factors around the DSB 19 . Notably, an A-KBM-like domain is present at the N-terminus of a recently identified inhibitor of the NHEJ pathway, CYREN(MRI), that also interacts with Ku80 20 (Figure 1a). Ku also associates with the Werner syndrome protein (WRN) that is involved in many aspects of DNA metabolism including NHEJ 21 .…”
Section: Introductionmentioning
confidence: 99%
“…For this aspect, we can solve the problem by utilizing a vector which can carry multiple gRNAs in the further study. Moreover, there are many other ways to improve the efficiency of gene repair, for example, adding small molecules, synchronizing the cell cycle, and adjusting delivery timing and methods . Besides, using ribonucleoprotein (RNP) delivery of Cas9 with gRNAs consistently can increase activity in cells and then enhance the efficiency …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are many other ways to improve the efficiency of gene repair, for example, adding small molecules, synchronizing the cell cycle, and adjusting delivery timing and methods. [29][30][31] Besides, using ribonucleoprotein (RNP) delivery of Cas9 with gRNAs consistently can increase activity in cells and then enhance the efficiency. 19,31 Since gRNA can target similar sequences in a genome, it is possible to have off-targets when we use SpCas9 system.…”
Section: Discussionmentioning
confidence: 99%